Effect of monensin supplementation on conjugated linoleic acid content in the milk - TYAGI, AMRISH; KAUR, HARJIT; KEWALRAMANI, NEELAM; SINGHAL, K K (The Indian Journal of Animal Sciences, 2011)
Multiparous Murrah buffaloes (16) and cows (16) in their early stage of lactation were randomly divided into 2 groups of 8 animals each (groups 1 and 2 for buffaloes and groups 3 and 4 for cows) to study the effect of monensin supplementation on conjugated linoleic acid content in their milk. Animals in groups 1 and 3 were offered maize forage, wheat straw and concentrate mixture and animals in groups 2 and 4 were supplemented with ionophore, i.e. 200 mg monensin sodium/d. Nutritional requirements of the animals were fulfilled as per standard requirements for 90 days of experimental period. Concentrate mixture contained more linoleic acid as compared to maize fodder (14.22 vs 3.54 mg/ g dry sample); whereas linolenic acid was more in maize as compared to concentrate mixture (6.82 vs 1.32 mg/g dry sample). After an adaptation period of 30 days, the milk samples were collected at fortnightly intervals and analyzed for milk fat, solid not fat, total solids and milk protein. Milk sample (100 ml) from each buffalo (morning and evening milking) and cow (morning, afternoon and evening milking) was collected at fortnightly interval and pooled for fatty acid analysis including CLA. Daily milk yield averaged 7.19 and 6.91 kg in buffaloes and 10.96 and 10.67 kg in cows, in the two respective groups. There was no effect of monensin supplementation on the milk yield of cows and buffaloes. Broad milk composition was not affected by monensin supplementation in both the species. Total CLA content averaged 6.2 and 7.1 mg/g fat in buffaloes and 6.8 and 8.1 mg/g fat in cows in the 2 two respective groups showing an increase of 14.51 and 19.11% due to monensin supplementation in the two species, respectively, indicating the beneficial effect of monensin supplementation on CLA content.